Destructive and minor destructive tests on masonry buildings: Experimental results and comparison between shear failure criteria. (28th February 2019) - Ferretti, Francesca; Ferracuti, Barbara; Mazzotti, Claudio; Savoia, Marco
Highlights: Comparison between results of minor destructive and destructive tests. Calibration and comparison of shear failure criteria for the masonry typologies. Use of different tests for reliable calibration of Mohr-Coulomb's failure domain. Shear behavior mainly governed by the local properties of the mortars. Indications about a proper planning of experimental campaigns on existing buildings. Abstract: In this paper, an extensive experimental campaign conducted on existing masonry buildings is presented. The main objective of this activity was to study the shear behaviour of masonries constituted by clay bricks and lime-based mortar evaluating the most suitable techniques applicable to get reliable information on the material mechanical properties. Minor destructive tests (MDT) and destructive tests (DT) were performed on eight masonry buildings, damaged by the 2012 Emilia earthquake (Italy). The tests results are here presented and discussed, focusing on the strength parameters obtainable from each test type and on the definition of appropriate failure domains. The strength predictions are finally compared with the outcomes of full-scale destructive tests.